Anxiety In Oscar Wilde's An Ideal Husband Drama (1895):A Psychoanalytic Approach - Setyonugroho, Aris (2012)
The major problem of this study is how anxiety is reflected in Sir Robert Chiltern's personality. The aim of this study is to analyze Oscar Wilde's An Ideal Husband drama based on Psychoanalytic Perspective. This study focuses on the major characters, namely Sir Robert Chiltern. The method of data collection is qualitative method. This study uses two data sources, namely primary and secondary data source. The primary data source is the script of the play itself, while the secondary data source includes books and other data that have relationship with the research. Technique of the Data Collection is library research, while the technique of Data Analysis in this study is descriptive. Based on the psychological analysis, it is clear that in An Ideal Husband drama Oscar Wilde is demonstrating a psychological phenomenon, in which an individual is experiencing anxiety and making efforts for coping with the anxiety.